PHYSICAL CHANGES OF SURIMI MUJAIR FISH (Oreochromis mossambicus.L) LONG EFFECT AND COLD STORAGE TYPES (Edible: Jurnal Penelitian Ilmu-ilmu Teknologi Pangan, 2022)
Surimi is one of the processed products from fisheries and is in great demand by some people in Asian countries. Our research analyzes changes in the physics of the surimi tilapia fish (Oreochromis mossambicus L.) caused by the effects of time and type of cold storage. Our research was carried out in the laboratory of the Palembang Industrial Research and Standardization Center for 2 months. This study used a Split Plot Design, namely two plots with cold storage as the main plot with two treatments (storage with freezer and using ice) and storage time as subplots with four treatments (0 day, 3 day, 6 day and 9 day storage). ), thus forming eight treatment combinations and repeated three times. Parameters observed are. Physical tests include elasticity tests and EMC (Expressible Moisture Content) tests. The type of storage has a very significant effect on the EMC power of tilapia surimi produced. The lowest EMC power was found in treatment P1 (freezer storage) with a value of 15.42%. Storage time has a very significant effect on the EMC power of tilapia surimi produced. The lowest EMC power was found in the W0 treatment (0 day storage) with a value of 13.82%. The interaction between species treatment and storage time had a very significant effect on the EMC power of tilapia surimi produced. Low EMC power was found in the P1W0 treatment interaction (type of freezer storage and 0 day storage) with a value of 13.84%.